Documentation-as-code for Interface Control Document Management in Systems of Systems: a Technical Action Research Study - Cadavid, Héctor; Andrikopoulos, Vasilios; Avgeriou, Paris (Springer, 2022)
The architecting of Systems of Systems (SoS), that is, of systems that emerge from the cooperation of multiple independent constituent systems, is a topic of increasing interest in both industry and academia. However, recent empirical studies revealed what seems to be an overlooked aspect of the architecting of SoS that is linked to major integration and operational issues: the interplay between the various disciplines involved in such an architecting process. This aspect becomes particularly relevant for the management of the interfaces between the SoS constituents, where such disciplines inevitably meet. In this paper, we present the results of the f irst cycle of a Technical Action Research (TAR) study conducted in cooperation between the authors and a group of practitioners involved in the long-running architecting process of a largescale radio astronomy SoS project. This TAR is aimed at exploring potential improvements of the document-centered interface management approach currently followed in this project by adopting elements of the documentation-as-code philosophy, which is widely adopted in the domain of software systems. As a result, a working proof-of-concept of an ICD (Interface Control Document) management approach was developed by the researchers and evaluated by the practitioners. The results of the study and the corresponding lessons learned are reported in this work.

La arquitectura de Sistemas de Sistemas (SoS), es decir, de sistemas que surgen de la cooperación de múltiples sistemas constituyentes independientes, es un tema de creciente interés tanto en la industria como en la academia. Sin embargo, estudios empíricos recientes revelaron lo que parece ser un aspecto pasado por alto de la arquitectura de SoS que está vinculado a importantes cuestiones operativas e de integración: la interacción entre las diversas disciplinas involucradas en dicho proceso de arquitectura. Este aspecto se vuelve particularmente relevante para la gestión de las interfaces entre los componentes del SoS, donde dichas disciplinas inevitablemente se encuentran. En este artículo, presentamos los resultados del primer ciclo de un estudio de Investigación de Acción Técnica (TAR) realizado en cooperación entre los autores y un grupo de profesionales involucrados en el proceso de arquitectura de largo plazo de un proyecto SoS de radioastronomía a gran escala. Este TAR tiene como objetivo explorar posibles mejoras del enfoque de gestión de interfaz centrada en documentos que se sigue actualmente en este proyecto mediante la adopción de elementos de la filosofía de documentación como código, que se adopta ampliamente en el dominio de los sistemas de software. Como resultado, los investigadores desarrollaron una prueba funcional de concepto de un enfoque de gestión ICD (Documento de control de interfaz), que los profesionales evaluaron. Los resultados del estudio y las correspondientes lecciones aprendidas se reportan en este trabajo.
Keywords: Ingeniería de sistemas de sistemas; Análisis de sistemas; Systems of Systems Engineering; System analysis; Integración de sistemas; Systems integration; Systems of Systems; Sistemas de sistemas Interfaz; Control Documentos; Control Documents; Documentation as code technical; Documentación como código Técnico; Action Research; Investigación para la Acción